2019
DOI: 10.28924/ip/jas.1872
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reinforcing Agro Dealer Networks on Agricultural Productivity in Niger

Abstract: Agricultural production in Niger has been plagued with low productivity and, as such, low incomes for the majority of the country's small-scale farmers, due largely to poor soil quality and arid climate conditions. Input-use is a crucial part of the solution to these problems. However, the rate of adoption remains low among farmers in Niger. One way in which they hoped to deal with this challenge was to train agro-dealers in three regions in Niger namely, Maradi, Tahoua and Zinder. This study sought to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Establishing demonstration plots and conducting trials on inputs were not commonly observed at agro-dealers' shops, indicating the need for training in these areas. Mamadou et al (2020) demonstrated that combining training with demonstration plots had a positive impact on the adoption of improved seeds by farmers. Therefore, supporting agro-dealers in establishing demonstration plots could be beneficial in promoting the adoption of new technologies and enhancing the overall impact of training efforts.…”
Section: Discrepancy In Agro-dealers' Skillsmentioning
confidence: 99%
“…Establishing demonstration plots and conducting trials on inputs were not commonly observed at agro-dealers' shops, indicating the need for training in these areas. Mamadou et al (2020) demonstrated that combining training with demonstration plots had a positive impact on the adoption of improved seeds by farmers. Therefore, supporting agro-dealers in establishing demonstration plots could be beneficial in promoting the adoption of new technologies and enhancing the overall impact of training efforts.…”
Section: Discrepancy In Agro-dealers' Skillsmentioning
confidence: 99%